Pengaruh Waktu Terhadap Temperatur Aktivasi dari Kulit Pisang (Musa paradisiaca L.) dalam Pembuatan Katalis - Yuni Kurniati; Eka Lutfi Septiani; Okky Putri Prastuti; Victor Purnomo; Sri Sugmah Nur Dewi; Imam Mahmuddin (Jurnal Teknik Kimia dan Lingkungan, 2020)
Banana peels include agricultural waste that contains lignocellulosic components (holocellulose and lignin) and carbohydrate content which is quite high. Banana peel is quite potential to be used as a substrate in producing catalysts. Acid catalyst is one type of catalyst that plays an important role in chemical processes. Chemical activation is the process of breaking the carbon chains of organic compounds by using chemicals. In this way, the activation process is carried out using chemicals (activators) as activating agents. This study aims to study the effect of activation temperature temrhadao from the optimum mass ratio of carbon-KOH in the synthesis process of banana skin charcoal based catalysts so as to produce a catalyst with the most optimal characteristics, and calcination temperature as a physical chemical process in the synthesis of banana skin charcoal based catalysts. The method of making the catalyst is done by calcination to decompose the carbon source into carbon so that the composite is formed according to the temperature that has been varied. After forming carbon-KOH composite, then sulfonation is carried out using concentrated sulfuric acid according to the specified temperature. Activation with KOH at activation temperatures of 300°C, 350°C and 400°C. In this research, the activation process can run optimally at temperatures of 300 °C, 350 °C, and 400 °C which are characterized by the presence of white smoke that has not come out anymore because carbon has reacted with KOH.